2022
DOI: 10.1007/s00167-022-06989-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute clinical evaluation for syndesmosis injury has high diagnostic value

Abstract: Purpose To determine the diagnostic value of injury history, physical examination, six syndesmosis tests and overall clinical suspicion for syndesmosis injury. Methods All athletes (> 18 yrs) with an acute ankle injury presenting within 7 days post-injury were assessed for eligibility. Acute ankle injuries were excluded if imaging studies demonstrated a frank fracture or 3 T MRI could not be acquired within 10 days post-injury. Standardized injury histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…MRI provides a more accurate diagnosis of acute syndesmotic injuries and can detect aberrant edema signals and ligament misalignment. 3 However, MRI is less accurate in patients with chronic injuries. 26 One study showed that CAI accompanied by chronic synovitis also resulted in localized strong signals in the syndesmotic region, which may compromise the λ sign’s ability to identify combined injuries in CAI patients.…”
Section: Discussionmentioning
confidence: 99%
“…MRI provides a more accurate diagnosis of acute syndesmotic injuries and can detect aberrant edema signals and ligament misalignment. 3 However, MRI is less accurate in patients with chronic injuries. 26 One study showed that CAI accompanied by chronic synovitis also resulted in localized strong signals in the syndesmotic region, which may compromise the λ sign’s ability to identify combined injuries in CAI patients.…”
Section: Discussionmentioning
confidence: 99%
“…A total of seven injury history variables were recorded during acute and delayed clinical evaluation using a previously described form [3]: (1) Injury [new/recurrent], (2) Occasion [game/training/non‐sports injury], (3) Contact [contact/non‐contact], (4) Mechanism of injury [inversion/eversion/external‐rotation/internal‐rotation], (5) Perceived presence of swelling [yes/no], (6) Perceived ankle instability [yes/no] and (7) Sensation of pain radiating up the leg [yes/no].…”
Section: Methodsmentioning
confidence: 99%
“…Nine standardized clinical tests were recorded during acute and delayed physical examination using a previously described standardized form [3]: (1) Presence of haematoma [yes/no], (2) Tenderness to palpation [lateral/medial/anterior/posterior], (3) Ability to walk normally [yes/no], (4) Ability to walk on toes [yes/no], Ability to walk on heels [yes/no], (5) Passive range of motion in dorsal flexion, plantar flexion, inversion and eversion [full/restricted/painful], (6) Presence of swelling [yes/no], (7) Swelling site [laterally/medially/anterior/posterior/syndesmosis], (8) anterior drawer test [Grades 0–2] and (9) talar tilt test [Grades 0–2]. The anterior drawer test and the talar tilt test were graded as Grade 0: normal; Grade 1: mild laxity; and Grade 2: moderate to gross laxity [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations